Axial rotation affects the cognitive characteristics of spatial ability - Feng, Tian; Zhang, Fuchun; Liu, Jinzhao; Liang, Manqi; Li, Yawei (Frontiers in Psychology, 2024)
Purpose To test spatial ability in athletes with different axial rotation experience and analyze their behavioral data to explain the cognitive mechanisms of spatial ability in athletes. Methods Experiment 1: A total of 147 athletes were selected for the paper-and-pencil mental rotation test (MRT). The athletes were separated according to three sport types: open high-spatial (OH) sport, closed high-spatial (CH) sport, closed low-spatial (CL) sport. Spatial ability testing with a two-factor mixed experimental design of 3 (sport type) × 2 (stimulus type). Experiment 2: In this study, 47 players were selected for computerized mental rotation test, with a three-factor mixed experimental design of 3 (sport type) × 2 (angle: 45°, 90°) × 3 (rotational axis: left–right axis, up–down axis, and front–back axis). Repeated-measures ANOVA was performed to evaluate the data. Results (1) The CH group and OH group outperformed the CL group in the non-embodied task (all ps < 0.003) and the CH group was better than the other groups in the embodied and tasks (all ps < 0.008). (2) Under 45° rotational conditions, the reaction time (RT) for the left–right (LR) and up–down (UD) axes were shorter than that for the front-back (FB) axis (all ps < 0.026). However, under 90° conditions, the RT for FB < LR < UD, with superior accuracy and rotational speed for the FB axis than for the LR and UD axes (all ps < 0.034). (3) Male players from the CH and CL groups had shorter RTs than did those from the OH group at both angles (all ps < 0.047). For female players, the CH group presented a shorter RT than the OH and CL groups did at 90° (all ps < 0.006). (4) No sex difference was found for paper and pencil MRTs, but a male advantage existed only in the CL group for computerized MRTs (p = 0.005). Conclusion The motor skills associated with axial rotation could promote mental rotation performance and compensate for sex differences in mental rotation ability.